An Overview of the Bioactivity of Spontaneous Medicinal Plants Suitable for the Improvement of Lung Cancer Therapies - Lidia-Ioana Virchea; Adina Frum; Cecilia Georgescu; Bence Pecsenye; Endre Máthé; Monica Mironescu; Mihai-Tudor Crăciunaș; Maria Totan; Ciprian Tănăsescu; Felicia-Gabriela Gligor (Pharmaceutics)
Lung cancer is the second cause of death in the world, being the most common type of cancer. Conventional therapies are not always recommended due to the particularities of patients. Thus, there is a need to develop new anticancer therapeutic agents. Medicinal plants constitute a source of bioactive compounds with therapeutic potential in lung cancer. The purpose of our narrative review is to evaluate and summarize the main studies on the cytotoxic effects of ten medicinal plants and their extracts, volatile oils, and bioactive compounds. We have also included studies that reported protective effects of these natural products against chemotherapy-induced toxicity. Studies were identified by assessing five databases using specific keywords. The investigated natural products possess cytotoxic effects on lung cancer cell cultures. Several mechanisms of action have been proposed including cell death by apoptosis, necrosis or autophagy, cell cycle arrest, the modulation of signaling pathways (PI3K/Akt and MAPK), the inhibition of migration, invasion and metastasis, antiangiogenesis, and targeting inflammation. Different bioactive compounds exhibit protective effects against chemotherapy-induced toxicity. Studies have shown promising results. To develop new therapeutic agents useful in treating lung cancer, the plants included in this review should be more deeply investigated to reveal their molecular mechanisms of action.